(untitled) (Academicia Globe: Inderscience Research, 2023)
This article discusses methods for solving systems of linear algebraic equations. The differences between the methods and their solutions, the Gaussian method of solving systems, the principles of implementing the Gaussian method for solving a system of linear equations in the Python programming language are presented.